Hepatic Arterial Infusion and Systemic Chemotherapy for Breast Cancer Liver Metastases. Issue 1 (23rd November 2012) - Ang, Celina; Jhaveri, Komal; Patel, Dina; Gewirtz, Alexandra; Seidman, Andrew; Kemeny, Nancy
Abstract Hepatic failure from breast cancer liver metastases (BCLM) is a major cause of morbidity and mortality. We reviewed the treatment histories and outcomes of nine patients with heavily treated BCLM, who received hepatic arterial infusion (HAI) of floxuridine (FUDR)/dexamethasone (Dex) and systemic chemotherapy at our institution. Patients received a median of five (range 1–15) HAI treatments. There were seven (78%) objective responses. Four patients had grade 3 elevations in liver enzymes attributable to HAI. There were no treatment‐related deaths. Median hepatic and extrahepatic time to progression on HAI were both 6 months. Median survival after starting HAI was 17 months (range 1–115). Median overall survival from the original breast cancer diagnosis was 110 months (range 52–248). One patient is alive with stable disease on systemic therapy alone. HAI and systemic chemotherapy is feasible and can benefit selected patients with BCLM, who have progressed on prior therapies. Patients require close monitoring for treatment‐limiting toxicities.